2005
DOI: 10.1093/sleep/28.10.1271
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Dependent Treatment of Delayed Sleep Phase Syndrome with Melatonin

Abstract: These results indicate that melatonin advances the circadian clock and sleep in patients with DSPS in a phase-dependent manner. This is the first study that reports a relationship between timing of melatonin administration and phase changes in patients with DSPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(134 citation statements)
references
References 34 publications
4
128
0
2
Order By: Relevance
“…In the first use of melatonin in patients with DSPS, it was found that when administered 5 h before sleep onset for a period of 4 weeks, melatonin (5 mg) advanced sleep onset and wake times compared with placebo (Dahlitz et al, 1991), which was later confirmed by Nagte gaal et al (1998) and Mundey et al (2005), and is most effective in DSPS patients with shorter habitual sleep time and later clinical onset (Kamei et al, 2000).…”
Section: Implications For the Treatment Of Insomnia And Circadian mentioning
confidence: 86%
“…In the first use of melatonin in patients with DSPS, it was found that when administered 5 h before sleep onset for a period of 4 weeks, melatonin (5 mg) advanced sleep onset and wake times compared with placebo (Dahlitz et al, 1991), which was later confirmed by Nagte gaal et al (1998) and Mundey et al (2005), and is most effective in DSPS patients with shorter habitual sleep time and later clinical onset (Kamei et al, 2000).…”
Section: Implications For the Treatment Of Insomnia And Circadian mentioning
confidence: 86%
“…Melatonin is widely used to treat various sleep disorders [119][120][121][122][123][124][125][126][127][128][129][130], including disorders associated with delayed phase sleep syndrome [119][120][121], periodic sleep disorders in blind patients [122][123][124][125] and sleep and behavioral disorders in children with severe brain damage [126][127][128][129]. In a randomized double-blind, placebo-controlled study [130], melatonin was shown to improve sleep efficiency and sleep latency [130] in cystic fibrosis (CF) patients, a chronic progressive disorder characterized by repeated episodes of respiratory distress and sleep disturbances [130].…”
Section: Role Of Melatonin In Maintaining and Restoring Human Healthmentioning
confidence: 99%
“…[29] Evening administration of melatonin (0.3-5mg) between 7pm and 8pm shifts circadian rhythms to an earlier time. [29,30] …”
Section: Delayed Sleep Phase Syndrome (Dsps)mentioning
confidence: 99%
“…Participants unsuitable (n= 5) [26][27][28][29][30] Insufficient data for analysis (n= 2) [31,32] Inappropriate method and data collection (n= 4) [33][34][35][36] No clear comparison group (n= 4) [37][38][39][40] Number of studies included in review (n=13) [41][42][43][44][45][46][47][48][49][50][51][52] Publications handpicked (screening reference list) (n= 2) …”
mentioning
confidence: 99%